2016
DOI: 10.14687/jhs.v13i3.4113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of perceived stress levels of kick-boxers based on age and gender variables / Yaş ve cinsiyet değişkenlerine göre kick boks sporcularının algılanan stres düzeylerinin incelenmesi

Abstract: The purpose of this research is to assess the perceived stress levels of kick boxers based on age and gender variables. 124 kick-boxers (68 female and 56 male) who participated in Interuniversity Kick Box Championship Turkey (Low-kick, Full Contact and Point

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This research study is not in parallel with the results of these research studies concerning the age variable. Taş (2013); Bayram et al (2016); Eraslan (2016) and Hancıoğlu (2017) did not detect a significant difference in the stress perceptions concerning the age variable. This study is in parallel with the results of these research studies in terms of age variable.…”
Section: Discussionmentioning
confidence: 91%
“…This research study is not in parallel with the results of these research studies concerning the age variable. Taş (2013); Bayram et al (2016); Eraslan (2016) and Hancıoğlu (2017) did not detect a significant difference in the stress perceptions concerning the age variable. This study is in parallel with the results of these research studies in terms of age variable.…”
Section: Discussionmentioning
confidence: 91%
“…Kaufman (19) found in his study with runners that being a runner for longer years predicted stress negatively. In the study conducted with the athletes participating in the Turkish Universities Kick Boxing Championship, it was determined that there was a statistically significant difference in the perceived stress levels according to their sports experiences (9). The analysis of the data revealed that there was no statistically significant difference in the perceived stress levels, both in the general scale and its sub-dimensions, among the individuals participating in the study in relation to the variable of competition success.…”
Section: Discussionmentioning
confidence: 94%